원위 경골 및 비골에 발생한 만성 재발성 다발성 골수염 - 김전교(Jeon-Gyo Kim); 곽희철(Heui-Chul Gwak); 허민영(Min Young Her); 김동균(Dong-Gyun Kim) (The journal of the Korean Orthopaedic Association, 2015)
만성 재발성 다발성 골수염은 비감염성 염증성 골병변으로 주로 소아와 청소년에게 발생하는 질환이다. 임상적으로 모호한 골성 동통을 호소하며, 방사선학적 소견 및 조직학적 소견이 감염성 골수염과 유사하다. 또한 비교적 드문 질환으로서 다른 질환과의 감별이어려워 종종 오진을 할 수 있다. 본원에서 11세 남아의 원위 경골 및 비골에 발생한 만성 재발성 골수염 1예를 경험하였기에 문헌 고찰과 함께 보고하고자 한다. Chronic recurrent multifocal osteomyelitis (CRMO) is a non-infectious inflammatory bone disease that occurs mainly in children and adolescents. The clinical presentation shows imprecise bone pain, while radiologic findings and histologic exam are similar to those of infectious osteomyelitis. It is a rare disease, which is difficult to distinguish from other diseases, therefore it could be misdiagnosed. We report on a case of CRMO on the distal tibia and fibula in an 11-year-old boy. KCI Citation Count: 0